Challenges of distance learning at the universities of Georgia during the covid-19 pandemic - Tengiz Verulava; Kakha Shengelia; Giorgi Makharashvili (Universidade Estadual de Maringá, 2024)
Besides many health problems and challenges, the covid-19 pandemic had a major impact on social, economic, political, and educational processes. The study aims to assess the consequences of distance learning as a result of the pandemic from the perspective of students and teachers. Quantitative research was conducted. Respondents evaluated the process of distance learning positively since they had a satisfactory opportunity to attend lectures from any location, thus it saved costs, they learned new skills, gained valuable experience, and had more free time left than ever before. Using the Likert scale, the distance learning process was positively assessed by students (3.2 points) and teachers (3 points). The majority of students (n = 288, 69%) prefer the hybrid model, which combines online learning and face-to-face methods, as it considered students' own choices in a superior way. Respondents pointed out some deficiencies such as limited communication, technical access difficulties, low quality and malfunction of internet access, inconvenient environment, student's involvement process, and complicated social relationships. Despite some challenges, students and teachers could adapt to the new learning methods of full distance learning. The majority of students and lecturers agreed with hybrid learning which combines online learning and face-to-face methods. The covid-19 pandemic changes not only the utilization of technology in education but the pedagogy strategies in the future.